Sementes cerâmicas radioativas com Ho-166 E Sm-153 com perspectiva de uso em braquiterapia - Eduardo Sarmento Valente (2010)
This work aimed to characterize physically, chemically and radioactively ceramics seeds with holmium and samarium embedded in ceramic matrix produced by sol-gel route. Biological response of HeLa cells was investigated macroscopically in vitro under the exposure to radiation of Ho-166 and Sm-153. The dispersal of radioactive material in simulated body fluid (SBF) was made and the dose rate and total dose deposited in the volume delimited by the range of particles in the water was calculated. The methodology used in physical, chemical and nuclear characterization was based on the following techniques: atomic emission spectrometry, neutron activation analysis, gamma spectrometry,X-ray fluorescence spectrometry and X-rays diffraction. In addition to the solubility in SBF, an in vivo pilot study assessed the dispersion of radioactive seeds implanted in rabbit muscle tissue. Four experiments were prepared to investigate the biological response in vitro, inwhich radioactive seeds were placed directly in contact with the cells in confluent culture flasks. The first two were done with seeds activity of 3.7 MBq (0.1 mCi) for the Sm-153 and 11.1 MBq (0.3 mCi) for Ho-166. There were no concerns with spatial positioning for seeds inthose early experiments. The subsequent experiments were performed with activity ranging from 37 MBq (1 mCi) and 111 MBq (3 mCi) and with defined position of the seeds in the flask. The results showed the presence of halos with maximum diameter of 8 mm around theseeds where there was a drastic reduction in the number of viable cells as a result of the effects of radiation. The calculation of dose deposited in water as well as the dose rate calculation of during handling of the seeds for an implant followed the methodology established by MIRD. These calculations found dose rates ranging from 7 to 19 Gy/h and